TRANSLATION ERRORS IN UNDERGRADUATE SCIENTIFIC WRITINGS: A CORPUS-BASED STUDY - Siregar, Roswani; Subagiharti, Heni; Handayani, Diah Syafitri; Sutarno, Sutarno; Hariani, Farida; Andriany, Liesna (Universitas Islam Sumatera Utara (UISU), 2025)
This study investigates translation errors found in 100 undergraduate thesis abstracts sourced from five Indonesian universities, with particular attention to syntactic, semantic, and miscellaneous error types. The data were collected from institutional online repositories, and all identifying information related to the authors was removed to ensure anonymity. Only the main bodies of the abstracts were used as the corpus for analysis. The findings reveal that the majority of errors fall under the syntactic category, including incorrect use of tenses, prepositions, and punctuation. Semantic errors, such as literal translations, meaning deviations, and unnecessary additions, were also frequently observed. These errors largely stem from students’ limited understanding of English grammar and translation strategies. The study highlights the importance of strengthening translation competence in undergraduate curricula. By systematically identifying and analyzing these common errors, the research provides valuable insights for improving the teaching of academic translation and suggests the integration of targeted translation materials in English language instruction at the tertiary level.